THE ROLE OF MEDIA LITERACY IN THE FUNCTIONING OF ESTONIA'S SYSTEM FOR COUNTERING FOREIGN POLICY DISINFORMATION (Вісник: Міжнародні відносини, 2025)
Background. The contemporary information environment, shaped by the rapid advancement of artificial intelligence and digital communication platforms, has transformed disinformation into a systemic threat of global scale, particularly for democratic states. In this context, Estonia – drawing upon its own geopolitical experience – has developed one of the most consistent and institutionalized models for countering foreign policy disinformation. This article aims to examine the operational mechanisms of Estonia’s information security system, with particular emphasis on the role of media literacy as a tool for enhancing societal resilience to information influence.Methods. The methodological framework of this study combines historical analysis to reconstruct the development of national information security policy, content analysis of strategic documents, legislative acts, and public communications, as well as institutional analysis of the activities of key governmental and civil society institutions.Results. Estonia has developed a multi-level system for countering disinformation, based on the "whole-of-society" approach. Legislative instruments provide authorities with the power to restrict the activities of hostile information resources. Media literacy is systematically integrated into the educational process, contributing to consistently high rankings in international indices. The active involvement of non-governmental organizations, particularly in outreach to Russian-speaking communities, enhances the system’s effectiveness. Estonia demonstrates the capacity for rapid response to foreign information threats. International cooperation, especially within the framework of the NATO Cooperative Cyber Defence Centre of Excellence, further strengthens collective security.Conclusions. The Estonian experience serves as a valuable example for countries seeking to strengthen national information security in the context of hybrid threats. Media literacy functions as a key element of societal resilience; however, further development of the system requires adaptation to emerging technological realities, strengthening of public-private partnerships, and greater consideration of the specific characteristics of target audiences.
Keywords: disinformation, information security, Estonia, media literacy, hybrid threats, national security, information influence.